THE ROLE AND LEGITIMACY OF AMIL ZAKAT IN THE DISTRIBUTION OF ZAKAT FITRAH: A CRITICAL STUDY BASED ON THE PERSPECTIVE OF MAQASID SHARIA AND INDONESIAN POSITIVE LAW: PERAN DAN LEGITIMASI AMIL ZAKAT DALAM DISTRIBUSI ZAKAT FITRAH: STUDI KRITIS BERDASARKAN PERSPEKTIF MAQASID SYARIAH DAN HUKUM POSITIF INDONESIA - Kasaful Khafi; M. Jamil; Dhiauddin Tanjung (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Zakat collectors in various regions in Indonesia carry out their duties without going through the oath process as prescribed by law. As a result, the invalidity of zakat can occur when the muzakki submits his zakat to an unsworn zakat collector, the absence of an oath on the zakat collector also has the potential to weaken public trust in zakat management. In Medan City, there is the National Zakat Collection Agency (BAZNAS) which is responsible for the appointment and oath-taking of the collector. Zakat management in the areas of Medan City is empowered using the Zakat Collection Unit (UPZ) which has been appointed and authorized by BAZNAS. And there are still many UPZs that are not appointed, authorized and registered still carrying out zakat management in the Medan City community. This study will analyze how the legal validity of the distribution of zakat fitrah by unsworn collectors is based on the perspective of zakat regulations in Indonesia and maqasid sharia, as well as the implications of government regulations on zakat management at BAZNAS and UPZ Medan City. The research in this thesis is a field research. This research is descriptive analytical with an normatif-empirical approach. Data collection techniques are by observation, interviews and documentation. After the data is collected, the author analyzes it qualitatively descriptively using the maslahah theory and legal effectiveness. The results of this study indicate that the legal validity of the distribution of zakat fitrah through unsworn amil based on the perspective of zakat laws in Indonesia is invalid, because based on applicable laws, zakat amil (UPZ) must be appointed and approved by the government and cooperate with the city BAZNAS. Meanwhile, based on the maqasid sharia of Jasser Auda, the distribution of zakat fitrah through unsworn amil is valid because the formation of the Zakat Collection Unit (UPZ) of the mosque is based on the welfare of the Muslim community. The implications of zakat regulations in Indonesia on the management of zakat at BAZNAS and UPZ and the community have a very good impact, because there is an increase in cooperation between UPZ and BAZNAS Medan City and the community around UPZ.